Uptake and Utilisation of Financial Inclusion Services Among Rural Youth Entrepreneurs: Progress or Regress? - Lelo, John Meku; Israel, Baraka (LPPM Universitas Terbuka, 2024)
This research provides comprehensive insights into how the uptake and utilization of formal and informal financial services are integrated into the business operations of rural youth entrepreneurs. A survey of 648 rural youth entrepreneurs across seven wards in the Iramba District of Tanzania was conducted. The findings reveal that while mobile money has emerged as the most widely adopted financial service, the utilization of formal financial services, such as bank accounts, insurance, and commercial bank services, remains low. Informal financial practices, including family support, informal lending, and home-based saving, continue to dominate the financial practices of rural youth entrepreneurs. The findings reveal a considerable room for improving the uptake and utilisation of formal financial services. Despite some progress, bridging the gap between formal and informal financial practices remains a critical challenge. The study concludes by offering policy recommendations to local governments and financial institutions, urging targeted interventions such as expanding internet connectivity, establishing community-based financial hubs, and implementing financial literacy programs to enhance access to formal financial services in rural areas. These efforts can be complemented by offering flexible financial products, such as micro-loans, low-fee accounts, low or no-cost transactions, and minimal documentation requirements, along with user-friendly digital banking platforms.